KEEFEKTIFAN KENDALI ORGANISASI: PERSPEKTIF TEORI AGENSI - Syafruddin, Muchamad (JURNAL BISNIS STRATEGI, 2000)
The objective of this article is whether the relationship between effectiveness of organizational control and agency costs exists. To examines those relathionship, explore to prior studies conducted, both empirical and analytical studies. However, the result of examination can be followed by empirical study.The result of examination shows that there is relationship between effectiveness of organizationalcontrol and agency costs. Effectiveness of organizational control is viewed based on the type of organizaitional control include of (I) behavior control, (2) output control, and (3) cultural and socialization control. Meanwhlle, agency costs are viewed based on (1) managerial stock ownership, (2) presence of accounting based bonus plan, (3) large individual percentage of stock ownership/diffusion of ownership, and (4) leverage.